An outbreak of Mycoplasma pneumoniae in children after the COVID-19 pandemic, Shanghai, China, 2023 - Zhu, Xunhua; Liu, Pengcheng; Yu, Hui; Wang, Libo; Zhong, Huaqing; Xu, Menghua; Lu, Lijuan; Jia, Ran; Su, Liyun; Cao, Lingfeng; Zhai, Xiaowen; Wang, Yi; et al. (Frontiers in Microbiology, 2024)
Background: During the coronavirus disease 2019 (COVID-19) pandemic, the infection of Mycoplasma pneumoniae (MP) decreased significantly. At the beginning of the summer of 2023, there was an increasing trend of MP infection in China and the MP pneumonia (MPP) is surging when it comes to the school season and lasts for several months which has attracted widespread attention. Objective: This study aims to investigate the prevalent characteristics of the MP and the difference between the COVID-19 pandemic and the post in Shanghai, China. Methods: The demographic information and the results of laboratory pathogen detection from July 2021 to May 2024 were collected and analyzed to find out the prevalent characteristics of MP. Two periods, during the COVID-19 pandemic and the post-pandemic, were divided and compared. The P1 genotyping and macrolide resistance-associated gene of 23s rRNA were detected using the remaining MP-positive samples. Results: During the COVID-19 pandemic, the prevalence of the MP has significantly decreased. Female children are more susceptible to MP infection than the male. The school-aged group (>6 years) had the highest infection rate. The rate of MP P1 genotype during post panel is higher than that during COVID-19 pandemic, which is dominant from July 2021 to May 2024, while the macrolide-resistant associated mutations (A2063G) keep high percentage during or post pandemic.